Headaches and its dependence from different factors in patients with temporal epilepsy at interictal period - O. S. Kurus; M. V. Nadezhdina; Ye. V. Osintseva; N. I. Skulskaya (Бюллетень сибирской медицины, 2010)
56 patients with temporal epilepsy (TE) at the age of (30.5 ± 10.0) years under the duration of the disease — (17.5 ± 10.7) years are examined. The examination included the anamnesis, somatic and neurological statuses, ultrasonic medical examination of brain vessels, the magneto-resonance tomography (MRI) of brain. Headaches (HA) among 80.4% patients with TE is revealed and its dependence from different factors is studied. The absence of gender differences, the dependence from the type TE, frequency of attacks and the duration of the disease among patients TE with HA are noticed, however the burdened neurological and obstetrical anamnesis, the presence HA among relatives, changes on data MRI of the brain, pathology of vertebral-basilar basin, the reduction and asymmetry of the index of the vessel resistance are observed. This amends the algorithm of the examination and treatment of patients with temporal epilepsy.